Iatrogenic Aortocoronary Arteriovenous Fistula following Coronary Artery Bypass Surgery: A Case Report and Complete Review of the Literature - Jonathan D. Gardner; William R. Maddox; Joe B. Calkins (Case Reports in Cardiology)
The case of a patient who presented with angina following a coronary artery bypass (CABG) operation during which the left internal mammary artery was inadvertently anastomosed to a cardiac vein is presented. The literature concerning previously reported cases of aortocoronary arteriovenous fistulas (ACAVF) due to inadvertent grafting of a coronary vein is reviewed and the significance of this complication is discussed. ACAVF due to inadvertent grafting of a coronary vein is a rare complication of CABG and may be a more common cause of graft failure than has previously been recognized. Distortion of cardiac anatomy, the presence of epicardial fat, and an intramyocardial course of the artery intended for grafting are predisposing factors. Some patients present with angina pectoris and heart failure whereas others have no symptoms. The diagnostic test of choice is coronary angiography. Cardiac MRI and CT have a limited role due to the smaller size and the more clearly defined course of these fistulas. Asymptomatic patients are simply observed since spontaneous closure of these fistulas is reported. Symptomatic patients can be treated with combined medical management and percutaneous methods.